IMPORTED INFLATION AND ITS IMPACT ON THE GENERAL BUDGET IN IRAQ (2004-2018) USING THE VAR MODEL - Asst prof. Dr. Bilal .M, Asst prof. Khalid.R, Lecture. Diaa.H (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims at analyzing the relationship between imported inflation and the general budget in Iraq (2004-2018).Monthly data is used for the purpose of achieving the aim of the study through the use of statistical and standard methods to obtain the most accurate results. By estimating and analyzing the relationship in the practical analysis in which VAR model is used, it is found that there is a direct relationship between imported inflation and expenditure in the general budget of Iraq during the study duration.